Cost-effectiveness study of therapeutic approaches for mucosal leishmaniasis - Janaína de Pina Carvalho; Gláucia Cota; Mariana Lourenço Freire; Endi Lanza Galvão; Sarah Nascimento Silva; Tália Santana Machado de Assis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to estimate the cost-effectiveness of four therapeutic approaches available for mucosal leishmaniasis in Brazil: miltefosine, meglumine antimoniate, combined with and without pentoxifylline, and liposomal amphotericin B. The perspective adopted was that of the Brazilian Unified National Health System (SUS). The outcome of interest was "cured patient", which was analyzed using a decision tree model. Estimates of direct costs and effectiveness were obtained from the scientific literature. Meglumine antimoniate alone was the base comparator strategy; liposomal amphotericin B showed an incremental cost-effectiveness ratio (ICER) of USD 7,409.13 per cured patient, and the combination of meglumine antimoniate with pentoxifylline presented an ICER of USD 85.13. Miltefosine was absolutely dominated, with higher cost and similar effectiveness when compared to meglumine antimoniate. Sensitivity analyses, varying the cost by ±25%, did not change the results. However, when the cost of miltefosine was estimated at less than USD 171.23, this strategy was dominant over meglumine antimoniate alone. The results confirm that treatment with liposomal amphotericin B remains the option with the highest ICER among the approaches analyzed. Miltefosine may be cost-effective based on the variation in the acquisition price, which deserves attention because it is the only available oral option. The non-accounting of other aspects prevent the use of these results immediately to support decision-making, but they point out the need to negotiate the prices of drugs available for mucosal leishmaniasis and indicates the need of encouraging technology transfer or other actions aimed at expanding the performance of the Brazilian national industrial complex.